PENINGKATAN LITERASI MASYARAKAT MELALUI POJOK BACA DIGITAL (POCADI) DINAS ARSIP DAN PERPUSTAKAAN DAERAH KABUPATEN BULELENG - Fridayanti, Niya (ACARYA PUSTAKA, 2024)
This research aims (1) to identify how Digital Reading Corners (POCADI) are used in an effort to increase people's reading interest in Buleleng Regency. (2) To find out the obstacles faced by the Buleleng Regency Regional Archives and Library Service in the Digital Reading Corner (POCADI) service. The research method used is a qualitative descriptive research method with informant collection techniques using purposive sampling and snow ball sampling. This research took place at the Digital Reading Corner (POCADI) of the Buleleng Regency Regional Archives and Library Service. Data collection in this research used observation, interview and document study techniques. The results of this research are that the Digital Reading Corner is a relevant innovation in supporting increased public literacy in the digital era. Its presence is based on the need to provide wider, faster and more efficient access to information through digital technology. This program not only provides wider access to information, but also empowers people to become more independent in seeking and utilizing knowledge. By continuing to increase collaboration and innovation, the Digital Reading Corner can become an effective model in supporting literacy development in Indonesia, as well as proving that libraries remain relevant amidst dynamic technological and social changes.